Feasibility of a Guided Inquiry-Based Biotechnology E-Module in Enhancing Scientific Literacy - Aisah, yuniar rakhmawati nur; yuliani, yuliani (Berkala Ilmiah Pendidikan Biologi (BioEdu), 2026)
Scientific literacy is essential in the 21st century, but Indonesian students' skills remain low, as shown by the 2022 PISA results. This study aims to develop a guided inquiry-based biotechnology E-Module to train students' scientific literacy skills. The research employed the ADDIE model and was conducted in the Biology Department of UNESA, with the module tested on 33 tenth-grade students at SMA Negeri 1 Puri. Validity was obtained through expert judgment, practicality was evaluated through observations of learning activity implementation and student responses, and effectiveness was assessed through improvements in pretest and posttest scores on scientific literacy skills. Data were analyzed using a quantitative approach. The validation results showed a 90% feasibility percentage, categorized as very valid. The E-Module demonstrated high practicality, with implementation scores of 98.05% and student response scores of 93.80%. Effectiveness was observed based on the N-Gain value for science literacy skills, with an average of 0.75, showing high improvement (≥ 0.7) in five of six scientific literacy indicators: identifying phenomena, formulating questions, designing experiments, collecting data, and drawing conclusions. One indicator, interpreting data and representing it in different forms, achieved an N-Gain score of 0.39 (moderate category). These results indicate that the E-Module effectively facilitates the development of scientific literacy skills. Therefore, the guided inquiry-based biotechnology E-Module is considered valid, practical, and effective in training students' scientific literacy skills.